Species Richness of Coral Reef Fishes in Sedili Kechil, Johor and Their Importance to Local People - Shahrul Zaman, Noor Syazwani; Kamarudin, Kamarul Rahim; Azahar, Muhammad Asyraff; Baharin, Ummi Nurain Akma; Mohd Fadzil, Siti Nursyuhada; Mohd Faid, Nurin Husnina; Azman, Hanis; Shahdan, Farhanah; Solehin, Siti Najihah; Akashah, Nursyamfarhani; Badrulhisham, Nur Sabrina; Legiman, Muhammad Idham; et al. (Journal of Sustainable Natural Resources, 2024)
Coral reef fish is a fish family that occur on every living coral reef, irrespective of its biogeographical location, that is, the core of modern reef fish fauna. However, no studies had been done in Johor marine area in Sedili Kechil despite their unique characteristics and importance to coral reefs and overall marine ecosystem. Therefore, this study aimed to record the species of coral reef fish found in Sedili Kechil, Johor with the aim to play a part in developing the Malaysian database of species richness of coral reef fish through species documentation in Sedili Kechil, Johor using bait fishing and net methods, and also to document the traditional knowledge of the local people regarding the coral reef fish. Genetic identification using cytochrome c oxidase subunit I (COI) mitochondrial DNA (mtDNA) gene was used as a complementary approach to the morphological species identification. The morphological and molecular classification proved that all 24 individuals obtained in this study belong to 18 species, 15 genera, 13 families, and 3 orders. A total of nine bidirectional CO1 barcode sequences were obtained from nine species, and the blast results for all the sequences, provide correct identification until the species level. The phylogenetic trees i. e neighbor joining tree (NJ) and maximum likelihood tree (ML) reconstructed using MEGA X software version 10.0.5 (BETA) further supported the species status. This is the first record of coral reef fishes from Sedili Kechil, Johor, Malaysia.